David Wendel Yandell : physician of old Louisville - Baird, Nancy Disher (Kentucky Bicentennial bookshelf., 1978)
David Wendel Yandell was the most distinguished physician of a family noted for its contributions to the medical profession over a period of generations. Like his father before him, Yandell taught for many years at the Medical Department of the University of Louisville. His years as a Confederate surgeon impressed upon him the horrifying consequences of the inadequate preparation of most physicians. Concerned especially about the need for practical training, Yandell waged a twenty-year campaign to expand clinic facilities and introduce intern programs at his own school and across the nation. H.